Relationship Undergraduate Medical Students' Summative Assessment and Learning Management System Readiness at A Public University in Indonesia - Wastucitra Cantika; Agus Sugiharto; Dewi Friska (Nusantara: Jurnal Pendidikan Indonesia, 2026)
Purpose – Good student readiness is needed, especially for medical students who are required to lifelong learning. This study aims to assess the relationship between student readiness related to LMS and the summative test score of the Primary Healthcare System module (SPKP) for students of the Faculty of Medicine at the University of Indonesia.Methods – This research is a cross-sectional design. A total of 191 respondents from fourth-year medical students of the Primary Healthcare System module, the Faculty of Medicine, at the University of Indonesia, participated in this research. The questionnaire consists of 5 dimensions and 10 questions with answers rated one to three. The measure of readiness is determined by the median value. The data were analyzed using the chi-square test. Findings – The findings revealed that 51.3% of students are ready to accept learning at LMS. The most obtained SPKP module summative score was B-, with a total of 31.4%. It was found that there was a relationship between student readiness related to the learning management system and a summative test score, with a P-value of 0.04 for the primary healthcare system module in medical students at the University of Indonesia. Research Implications – This research contributes to universities, lecturers that it is necessary to conduct technical system training at the beginning of the semester, provide easily accessible interactive modules, and strengthen infrastructure to support independent learning.